Causal overlap of the suspension of the employment relationship - De los Santos Esteves, Juan Miguel (2024)
The suspension of the employment relationship is a legal concept that is necessarily causal and temporary, and being properly a contingency of the employment contract, it can occur predictably or unpredictably. In this regard, what is known as the causal overlap of work suspension could be configured, which occurs in the presence of more than one valid cause that generates the suspension of the same employment relationship simultaneously. Therefore, after analyzing the main characteristics of work suspension: its causality and temporality, we will determine whether, in the case of the causal overlap of work suspension, the validity of the effects of the causes that generate the suspension of work and the legal effects on the employment relationship could be deferred or modified given the overlap of causes that generate both imperfect and perfect suspension of work simultaneously.